Lysotypes and plasmidial profile of Salmonella Serovar Typhimurium isolated from children with enteric processes in the cities of Rio de Janeiro, RJ, and Salvador, BA - Brazil Lisotipos e perfil plasmidial de Salmonella Serovar Typhimurium isoladas de processos entéricos infantis nas Cidades do Rio de Janeiro, RJ e Salvador, BA - Brasil - Marise Dutra Asensi; Arudy Penna Costa; Eliane Moura Falavina dos Reis; Ernesto Hofer (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
The lysotypes, plasmidial profiles, and profiles of resistance to antimicrobial agents were determined in 111 Salmonella Typhimurium strains isolated from feces and blood of children treated in Rio de Janeiro and in Salvador. Six distinct lysotypes (19, 41, 97, 105, 120 and 193) were recognized, with a predominance of lysotype 193 (59.7%) in Rio de Janeiro and of phage type 105 (38.4) in Salvador. Approximately 86.7% of the lysotype 193 strains presented multiple resistance to more than six antimicrobial agents, whereas 93% of lysotype 105 strains were fully susceptible. More than 90% of the strains presented plasmids distributed into 36 different profiles in Rio de Janeiro and into 10 profiles in Salvador. A 40 MDa plasmid was the most frequent (47%) in the strains from Rio de Janeiro, whereas a 61 MDa plasmid predominated (14.5%) in Salvador. Combined analysis of plasmid profile and classification into lysotypes (especially those belonging to types 105 and 103, proved to be more discriminatory than the other methods applied). Os lisotipos e os perfis de resistência a antimicrobianos e plasmidial foram caracterizados em 111 amostras de Salmonella Typhimurium isoladas de fezes e sangue de crianças atendidas nas cidades do Rio de Janeiro e Salvador. A lisotipia evidenciou seis tipos fágicos distintos (19, 41, 97, 105, 120 e 193) com uma predominância do lisotipo 193 (59,7%) na primeira cidade e do fagotipo 105 (38,4) na segunda. Cerca de 86,7% das amostras do lisotipo 193 apresentaram resistência múltipla para mais de seis antimicrobianos, enquanto que 93,3% de 105 foram totalmente sensíveis. Em mais de 90% das amostras, verificou-se a presença de plasmídios, distribuídos em 39 perfis diferentes nas do Rio de Janeiro e 10 nas de Salvador. Predominou o plasmídio de 40 MDa nas amostras do Rio de Janeiro (47%), enquanto o de 61 MDa (14,4%) prevaleceu em Salvador. A associação da análise do perfil plasmidial com a fagotipagem, principalmente naqueles pertencentes aos lisotipos 105 e 193, comprovou ser mais ...